The energy spectrum of cosmic rays beyond the turn-down around 1017 eV as measured with the surface detector of the Pierre Auger Observatory - Binet, V. (2021)
Fil: Fil: Binet, V. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Física de Rosario (IFIR-CONICET); Argentina.